2021
DOI: 10.3390/polym13101615
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Interfacial Bonding Enhancement of Oil Palm Bio-Ash Nanoparticles Biocomposites

Abstract: The effect of incorporating different loadings of oil palm bio-ash nanoparticles from agriculture waste on the properties of phenol-formaldehyde resin was investigated in this study. The bio-ash filler was used to enhance the performance of phenol-formaldehyde nanocomposites. Phenol-formaldehyde resin filled with oil palm bio-ash nanoparticles was prepared via the in-situ polymerization process to produce nanocomposites. The transmission electron microscope and particle size analyzer result revealed that oil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Tao et al [59] (2019) Tensile strength-189% improved Cai et al [60] (2022) Tensile strength-57 MPa Abdullah et al [61] (2021) Internal bonding strength improved Hasan et al [62] (2021) Insulation properties-0.000494 W/ m.K Senthilkumar et al [63] (2020)…”
Section: Pf Nanocomposites Observations Pf/natural Fiber Composites O...mentioning
confidence: 99%
“…Tao et al [59] (2019) Tensile strength-189% improved Cai et al [60] (2022) Tensile strength-57 MPa Abdullah et al [61] (2021) Internal bonding strength improved Hasan et al [62] (2021) Insulation properties-0.000494 W/ m.K Senthilkumar et al [63] (2020)…”
Section: Pf Nanocomposites Observations Pf/natural Fiber Composites O...mentioning
confidence: 99%
“…Hence, developing alternative fillers generated from by-products or waste material is necessary to reduce the environmental pollution and replacing the current commercial fillers. These alternative fillers include oil palm ash, 13,14 rice husk ash, 15,16 waste Aquilaria crassna wood, 17 coconut shells, 18,19 macadamia shells, 20 and fly ash (FA). [21][22][23][24] By-products are produced as waste in commercial industries or biological manufacturing, where waste is defined as inefficient materials and activities that do not add value to the product.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have shown that nanometer-sized fillers can improve the performance of composites [20,[27][28][29][30]. Ball milling can be applied to produce nanoparticles or nanopowders [31]. Duration of milling or milling time is one of the important parameters in producing nanoparticles [32].…”
Section: Introductionmentioning
confidence: 99%